Perceptions of EFL Learners about Using an Online Tool for Vocabulary Learning in EFL Classrooms: A Pilot Project in Turkey. (14th October 2016) - Köse, TuĿçe; ÿimen, Eda; Mede, Enisa
Abstract: The purpose of this study is to investigate the effects of Quizlet, an online website, on vocabulary development of Turkish EFL learners enrolled in a preparatory program at a private university in Istanbul, Turkey. The participants were 43 preparatory students at the pre-intermediate and intermediate levels of proficiency. The study lasted for a whole teaching module consisting of 7 weeks. Within this process, for three weeks students studied and practiced the target words without using the online tool Quizlet. For the last four weeks students were weekly assigned with exercises from the online tool covering the units that they had learnt in the previous weeks. As for the data collection process, vocabulary quizzes were administered to the participants before and after the application of the treatment and the results were compared. Classroom observations, interviews and student records were also used so as to identify students⿿ perceptions of the online tool. The findings of the study revealed that majority of the students considered the online tool to be effective particularly at the initial stages of vocabulary learning considering L2 definitions, synonyms and pronunciation of the target words through repetition.